2021
DOI: 10.1111/crj.13353
|View full text |Cite
|
Sign up to set email alerts
|

Association of depression with improper use of inhaler devices by patients with obstructive disease

Abstract: Optimal management of respiratory diseases like asthma and chronic obstructive pulmonary disease, in patients of all ages, requires sufficient drug delivery to the airways by inhaler devices 1 ; a proper inhaling technique is also essential. Inhaler therapy is the most effective approach to treat respiratory disease patients; however, the reported proportion of patients using incorrect inhalation techniques varies widely, between 27% and 89%. 2,3 Patients should learn to use inhaler devices effectively to ensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…One study found a link between the presence of depression and the misuse of inhalers [64]. In this study, the presence of depressive symptoms, evaluated using the 21-question Beck Depression Inventory (BDI) scale, resulted in an approximate 22-fold increase in the risk of inhaler misuse [64].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study found a link between the presence of depression and the misuse of inhalers [64]. In this study, the presence of depressive symptoms, evaluated using the 21-question Beck Depression Inventory (BDI) scale, resulted in an approximate 22-fold increase in the risk of inhaler misuse [64].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Pun et al [81] found a correlation between the educational level and the correct use of the Rotahaler ® DPI, but this correlation was not found for a pMDI. Evaluation of the educational level was mainly based on schooling years, with varying thresholds between ≤6 years and <12 years characterizing lower education [64, 75, 82]. Duarte-de-Araújo et al [83] used a threshold of ≤3 years of school and combined this information with the Graffar Social Scale, a socioeconomic scale comprising five items, including educational level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of a long-term phase III pragmatic reallife trial conducted on a large general population have shown a significant decrease of the number of COPD exacerbations, although this did not reach the MCID 28 . Poor inhaler technique and nonadherence (primary or secondary) impair the efficacy of COPD drugs 29 , for this reason optimal disease control requires a careful selection by the physicians of one of the different types of devices [pressurized metered-dose inhaler (pMDI, to be used preferably with a valved holding-chamber), dry powder inhaler (DPI), soft mist inhalers, nebulizers] according to the clinical needs/features and preferences of the individual patient, and to regularly retrain and check the patient in the correct use of the device [30][31][32][33][34][35] . When present the treatment of depression of stable COPD patients may increase proper use of inhalers 36 .…”
Section: General Drug Treatment Recommendations For Stable Copd Patientsmentioning
confidence: 99%
“…Poor inhaler technique and nonadherence (primary or secondary) impair the efficacy of COPD drugs 28 , for this reason optimal disease control requires a careful selection by the physicians of one of the different types of devices [pressurized metered-dose inhaler (pMDI, to be used preferably with a valved holding-chamber), dry powder inhaler (DPI), soft mist inhalers, nebulizers] according to the clinical needs/features and preferences of the individual patient, and to regularly retrain and check the patient in the correct use of the device [29][30][31][32][33][34] . When present the treatment of depression of stable COPD patients may increase proper use of inhalers 35 . The use of electronic monitoring devices for inhalers to objectively measure adherence is promising 36 , as well as the use of digital devices to monitor various physiological parameters of patients during their usual everyday activities and to tailor medications and dosage to the specific needs of individual patients 37,38 .…”
Section: General Drug Treatment Recommendations For Stable Copd Patientsmentioning
confidence: 99%